2014
DOI: 10.1016/j.is.2012.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Mining frequent itemsets in a stream

Abstract: Mining frequent itemsets in a datastream proves to be a difficult problem, as itemsets arrive in rapid succession and storing parts of the stream is typically impossible. Nonetheless, it has many useful applications; e.g., opinion and sentiment analysis from social networks. Current stream mining algorithms are based on approximations. In earlier work, mining frequent items in a stream under the max-frequency measure proved to be effective for items. In this paper, we extended our work from items to itemsets. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Luckily, Calders et al [11] demonstrated that we can use the classic PAVA algorithm by Ayer et al [5] to solve this problem for every value of j in total O(n) time.…”
Section: Linear Approximation Algorithmmentioning
confidence: 99%
“…Luckily, Calders et al [11] demonstrated that we can use the classic PAVA algorithm by Ayer et al [5] to solve this problem for every value of j in total O(n) time.…”
Section: Linear Approximation Algorithmmentioning
confidence: 99%
“…Both supervised and unsupervised techniques have been employed to automatically adapt and construct event patterns. A widely used unsupervised learning technique is the frequency-based analysis of sequences of events (e.g., Yu et al [2004], Lee and Lee [2005], Vautier et al [2007], Álvarez et al [2010], and Calders et al [2014]). Frequency-based analysis is a promising approach for discovering unknown events in databases or logs, but it is limited to propositional learning.…”
Section: Distributed Event Recognitionmentioning
confidence: 99%
“…Further interestingness measures for episodes, either statistically motivated or aimed at removing bias toward smaller episodes, were made by Garriga [22], Gwadera et al [23,24], Calders et al [25], and Tatti [9]. All these methods, however, were limited to finding interesting episodes, and stopped short of discovering association rules between them.…”
Section: Related Workmentioning
confidence: 99%